El neoconstitucionalismo. Una definición y una taxonomía latinoamericana - Vicente Solano Paucay (Ius Humani. Jornal do direito, 2016)
In order to define some of the main elements of neo-constitutionalists theses, we must ask ourselves some fundamental questions that can help us to distinguish the relationship between this “tendency” and traditional legal theories. These questions will allow us to figure out the different notions denominated neo-constitutionalists in order of accomplishing the objective of identify and classify them. The first question would be related with the thesis of the connection between law and morality; the second question would have to review the thesis of the necessity of morality for the identification and validity of law; the third question has to explore the thesis where principles or constitutional values ​​refer to morality and its implicative thesis of how to apply the principles and rules. In this way, we can find into the neo-constitutionalists theses some convergences or divergences that may lead us to better clarify plausible criteria for the identification of transcendental elements. These elements denote if “neo-constitutionalism” is a new “theory” of the overriding law of dichotomy between non-positivism and legal positivism.